Electrochemical Corrosion Properties of Ternary Al and Quaternary Zr Added Bell Metal in 0.1M NaCl Solution - Sakib Al Razi Khan; Mohammad Ashfaq Hossain; Maglub Al Nur; Mohammad Salim Kaiser (Journal of Mechanical Engineering Science and Technology (JMEST), 2021)
The electrochemical corrosion property of ternary Al and quaternary Zr added Bell metal in 0.1M Sodium Chloride solution has been experimentally conducted at room temperature. Electrochemical impedance spectroscopy (EIS) method and Potentiodynamic polarization technique are used to carry out the electrochemical investigation. Microhardness test is also conducted for all three alloys and it reveals that Al addition increases the hardness of bell metal due to the formation of different intermetallic precipitates of Cu and Al. Optical Micrograph as well as Scanning Electron Micrograph have also been studied to characterize their surface condition. It is found that Zr addition refines the grain structure of the alloy and results in increase of hardness. The EIS study reveals that the corrosion resistance is seem to be augmented with the addition of ternary Al and quaternary Zr to bell metal. The potentiodynamic polarization curves disclose that both ternary Al added and quaternary Zr added alloy show better corrosion performance than the base bell metal alloy due to the formation of stable aluminium oxide film. The currentdensity (Icorr) of base bell metal showed higher value than both ternary Al added and quaternary Zr added bell metal alloys. The corrosion potential (Ecorr) and the open circuit potential (OCP) were seen to be moved to the more positive direction for the Al and Zr added alloys. Microstructure and SEM study of the alloys after corrosion revealed a formation of an oxide film on the surface of the ternary A and quaternary Zr added alloys, the probable cause of which is the presence of Al in the respective alloys.